Mammalian prey of Barn Owl (Tyto Alba) in southesastern Oaxaca, México. - Santos-Moreno, Antonio; Alfaro Espinosa, Ana María (Instituto de Ecología, A.C., 2009)
The analysis of pellet contents of Barn Owls from southeastern Oaxaca, Mexico, shows that mammals represent the main prey of this bird. We identified a minimum of 184 individuals from 2 orders, 3 families and 8 species of mammals. The greatest number of prey was from hispid cotton rat (Sigmodon hispidus), which represented 83.69% of the total individuals and 84.68% of the biomass of the sample. From the other 7 species included in the pellets, 3 were very uncommon species: the cozumelan golden bat (Mimon cozumelae), the false vampire bat (Vampyrum spectrum), and the Peter’s climbing rat (Tylomys nudicaudus). Bats represented 2.17% of prey number and 0.799% of the total biomass estimated in the sample. Comparisons of these results with the estimated abundances by standard trapping methods show differences. These results corroborate a general pattern of barn owl opportunistic predation over the locally most abundant species and bats as rare prey.